Prevalence Pattern of Extended Spectrum Beta-Lactamase (ESBL) Producing Escherichia coli in the Intestinal Flora of Milkfish - Dinara Safina Salsabillah; Kuntaman Kuntaman; Masfufatun Masfufatun; Putu Oky Ari Tania (Jurnal Biologi Tropis, 2026)
Escherichia coli is one of the gram-negative bacteria that produces the Extended Spectrum Beta-Lactamase (ESBL) enzyme and has a role in resistance to the beta-lactam group. The presence of E. coli bacteria that produce ESBL in food, especially in fish such as milkfish (Chanos chanos) poses a potential source of the spread of antimicrobial resistance (AMR) in humans. This study aims to determine the prevalence of ESBL-producing E. coli in the intestinal flora of milkfish sold in traditional markets in Surabaya City. This study used a descriptive observational method with a cross-sectional approach. There were 50 samples of milkfish intestines taken from several stalls in traditional markets randomly. Identification of E. coli bacteria by planting in MacConkey media with 4 µL/ml cefotaxime followed by the Double Disk Synergy Test (DDST). Of the 50 milkfish intestine samples used, 34 (68%) samples showed positive results for ESBL-producing E. coli. The high prevalence may indicate that the potential for the spread of antimicrobial resistance through the food chain, food hygiene management and controlling the use of antibiotics in fish farming need serious attention.